Religious Identities versus National Identity: an assessment of the views of syrian refugees in Brazil about National Identity Consciousness | Identidades Religiosas versus Identidade Nacional: uma avaliação sa visão dos refugiados sírios no Brasil sobre a Consciência de Identidade Nacional - Pires, Guilherme Di Lorenzo; Zahreddine, Danny (Mural Internacional, 2021)
Many analyses of the civil war in Syria see the religious divisions as one of the main aspects that explain its outbreak in 2011. According to this perspective, the conflict results from the dominance of subnational identities over national identity. This argument is now widely contested by civil war literature. This article endorses this contestation and seeks to evaluate the hypothesis that the incompatibility between social identities would weaken social cohesion in Syria. A questionnaire was distributed to Syrian volunteers in Brazil, addressing the importance and prominence of national and religious identities. The argument presented here is that a) there is not necessarily an incompatibility between religious identity and national identity; b) national identity is well established and widespread among Syrians; and c) despite not being the immediate cause of the conflict, the salience of religious identities makes them an important factor, among others, in social mobilization. Keywords: National Identity; Syria; Religious Identity. RESUMO Muitas análises sobre a guerra civil na Síria atribuem às clivagens religiosas um dos principais aspectos que explicam sua eclosão em 2011. Para essa perspectiva, o conflito seria resultado da primazia das identidades subnacionais sobre a identidade nacional. Esse argumento, contudo, é bastante contestado atualmente pela literatura em guerra civil. O artigo busca avaliar a hipótese de que a incompatibilidade entre identidades sociais seriam um fator de enfraquecimento da coesão social. Um questionário foi distribuído para voluntários sírios no brasil abordando a importância e a saliência das identidades nacionais e religiosas. O argumento aqui defendido é que a) não há necessariamente uma incompatibilidade entre identidade religiosa e identidade nacional; b) a identidade nacional é bem estabelecida e difundida entre os sírios; e c) apesar de não ser a causa imediata do conflito, a saliência das identidades religiosas faz com que elas sejam um vetor importante, entre outros, na mobilização social. Palavras-chave: Identidade Nacional; Síria; Identidade Religiosa. Recebido em: 14 jun. 2021 | Aceito em: 09 dez. 2021.